Effect of acidic agents on surface roughness of dental ceramics - Boonlert Kukiattrakoon; Chanothai Hengtrakool; Ureporn Kedjarune-Leggat (Wolters Kluwer Medknow Publications, 2011)
Background: An increase in surface roughness of ceramics may decrease strength and affect the clinical success of ceramic restorations. However, little is known about the effect of acidic agents on ceramic restorations. The aim of this study was to evaluate the surface roughness of dental ceramics after being immersed in acidic agents. Methods: Eighty-three ceramic disk specimens (12.0 mm in diameter and 2.0 mm in thickness) were made from four types of ceramics (VMK 95, Vitadur Alpha, IPS Empress Esthetic, and IPS e.max Ceram). Baseline data of surface roughness were recorded by profilometer. The specimens were then immersed in acidic agents (citrate buffer solution, pineapple juice and green mango juice) and deionized water (control) at 37°C for 168 hours. One group was immersed in 4% acetic acid at 80°C for 168 hours. After immersion, surface roughness was evaluated by a profilometer at intervals of 24, 96, and 168 hours. Surface characteristics of specimens were studied using scanning electron microscopy (SEM). Data were analyzed using two-way repeated ANOVA and Tukey's multiple comparisons (α = 0.05). Results: For all studied ceramics, all surface roughness parameters were significantly increased after 168 hours immersion in all acidic agents (P < 0.05). After 168 hours in 4% acetic acid, there were significant differences for all roughness parameters from other acidic agents of all evaluated ceramics. Among all studied ceramics, Vitadur Alpha showed significantly the greatest values of all surface roughness parameters after immersion in 4% acetic acid (P < 0.001). SEM photomicrographs also presented surface destruction of ceramics in varying degrees. Conclusion: Acidic agents used in this study negatively affected the surface of ceramic materials. This should be considered when restoring the eroded tooth with ceramic restorations in patients who have a high risk of erosive conditions.